Review of pediatric emergency care and the COVID‐19 pandemic - Ashley A. Foster; Theresa A. Walls; Kiyetta H. Alade; Kathleen Brown; Marianne Gausche‐Hill; Sophia D. Lin; Emily A. Rose; Timothy Ruttan; Sam Shahid; Annalise Sorrentino; Michael J Stoner; Muhammad Waseem; et al. (Journal of the American College of Emergency Physicians Open)
Abstract The coronavirus disease 2019 (COVID‐19) pandemic posed new challenges in health care delivery for patients of all ages. These included inadequate personal protective equipment, workforce shortages, and unknowns related to a novel virus. Children have been uniquely impacted by COVID‐19, both from the system of care and socially. In the initial surges of COVID‐19, a decrease in pediatric emergency department (ED) volume and a concomitant increase in critically ill adult patients resulted in re‐deployment of pediatric workforce to care for adult patients. Later in the pandemic, a surge in the number of critically ill children was attributed to multisystem inflammatory syndrome in children. This was an unexpected complication of COVID‐19 and further challenged the health care system. This article reviews the impact of COVID‐19 on the entire pediatric emergency care continuum, factors affecting ED care of children with COVID‐19 infection, including availability of vaccines and therapeutics approved for children, and pediatric emergency medicine workforce innovations and/or strategies. Furthermore, it provides guidance to emergency preparedness for optimal delivery of care in future health‐related crises.